2015
DOI: 10.1088/0957-4484/26/49/495501
|View full text |Cite
|
Sign up to set email alerts
|

Ionic screening effect on low-frequency drain current fluctuations in liquid-gated nanowire FETs

Abstract: The ionic screening effect plays an important role in determining the fundamental surface properties within liquid-semiconductor interfaces. In this study, we investigated the characteristics of low-frequency drain current noise in liquid-gated nanowire (NW) field effect transistors (FETs) to obtain physical insight into the effect of ionic screening on low-frequency current fluctuation. When the NW FET was operated close to the gate voltage corresponding to the maximum transconductance, the magnitude of the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…From the paper, a 0.001 M PBS system showed a current noise power density which was 70% noisier than in 0.1 M PBS buffer, while the current noise power density showed only small pH dependence. 132 Their results…”
Section: Signal-to-noise Ratio Enhancementmentioning
confidence: 99%
“…From the paper, a 0.001 M PBS system showed a current noise power density which was 70% noisier than in 0.1 M PBS buffer, while the current noise power density showed only small pH dependence. 132 Their results…”
Section: Signal-to-noise Ratio Enhancementmentioning
confidence: 99%
“…25 Experiments have shown a decrease in low frequency noise with increased ionic strength due to increased screening competition between the EDL and the semiconductor device. 26 Heitzinger et al suggested a different trend for DNA-sensing, in which they calculated an increase in the standard deviation of the FET channel current with ionic concentration due to an increasingly variable orientation of the DNA. 21 These studies show that addition of a biomolecule, such as DNA, can affect EDL dynamics to the extent that a response can be observed in the frequency domain that is not apparent in the time-domain, even under high ionic strength conditions.…”
Section: Importance Of Edl Structure and Ion Dynamics In The Interfacmentioning
confidence: 99%
“…Furthermore, in the LG system the effective FET capacitance (C eff ) could be described by a series connection of the EDL capacitance (C dl ) at the liquid-MoS 2 interface [31] and the quantum capacitance (C q ). Because a thick dielectric layer served as the back-gate dielectric in our back-gate FET systems, the geometrical capacitance (C ox ) could be considered as the predominant capacitance in this capacitive circuit.…”
Section: Wwwadvelectronicmatdementioning
confidence: 99%
“…where ε W and λ D are the permittivity in water and the Debye screening length, [31] respectively. Because of several reliability issues that arose when we exposed the MoS 2 FETs to aqueous solutions, the voltage applied to the liquid-gate electrode was maintained intentionally at a value as low as possible to avoid the electrochemical reaction at the MoS 2 surface.…”
Section: Wwwadvelectronicmatdementioning
confidence: 99%
See 1 more Smart Citation